Shocking Aspects of Canadian Labor Markets - Sutton, Bennett (IMF Working Papers; Working Paper ;, 2006)
We analyze the flexibility of the Canadian labor market across provinces in both an interand intra-national context using macroeconomic data on employment, unemployment, participation, and (for Canada) migration and real wages. We find that Canadian labor markets respond in a similar manner to their U.S. counterparts and are more flexible than those in major euro area countries. Within Canada, the results indicate that labor markets in Ontario and provinces further west are more flexible, particularly with regard to migration, while those further east are less so.